Group portrait of Sydney Grammar School pupils' cricket team and coach, Sydney, 29 October 1948, 5. (1948)
Pupil in middle holding a tablet with text 'MS B 1948' written on it.
Title devised by cataloguer from accompanying information.
Part of the collection: Newcastle Morning Herald and Miner's Advocate archive, 1900-1960.
Keywords: Sydney Grammar School -- Photographs; Students -- New South Wales -- Sydney -- Photographs; Cricket coaches -- New South Wales -- Sydney -- Photographs; Cricket -- New South Wales -- Sydney -- Photographs; Sydney (N.S.W.) -- Photographs